2011
DOI: 10.1002/pts.924
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of packaging and influences on waste

Abstract: An important area of focus for the reduction of domestic waste is packaging and food packaging specifically. At some point in the life of packaging in the consumers' home, the packaging goes through a transition from something of use, of value and of worth to the consumer to something that is no longer any of these. Being able to indentify attributes of packaging that might have an impact on this transitional point to change the use or value so that the packaging is re-used, recycled or composted rather than b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(94 citation statements)
references
References 8 publications
3
90
0
1
Order By: Relevance
“…For example, the research conducted by the Foundation for Reusable Systems assessed whether disposable or reusable packaging can save food from spoilage (Karst, 2013), and found that reusable packaging has an advantage of reducing the amount of packaging going to waste schemes and recycling processes due to its strength, consistent size and compatibility compared to one-way packaging. Langley et al (2011) confirmed that any products that fell into the reuse route were not thought of as waste by consumers. With regard to the environment, reuse is advantageous in several ways, according to the Industry Council for Packaging and the Environment (2009).…”
Section: Literature Reviewmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, the research conducted by the Foundation for Reusable Systems assessed whether disposable or reusable packaging can save food from spoilage (Karst, 2013), and found that reusable packaging has an advantage of reducing the amount of packaging going to waste schemes and recycling processes due to its strength, consistent size and compatibility compared to one-way packaging. Langley et al (2011) confirmed that any products that fell into the reuse route were not thought of as waste by consumers. With regard to the environment, reuse is advantageous in several ways, according to the Industry Council for Packaging and the Environment (2009).…”
Section: Literature Reviewmentioning
confidence: 75%
“…The project found that incentive is one of the important factors, together with the quality of packaging to be refilled, which can enhance reuse behaviour and that, as long as there is a good reason behind the reuse approach, consumers will not mind participating in the activity (Lofthouse et al, 2009). Langley et al (2011) conducted a real case study in the UK to determine how different packaging can encourage and discourage the consumers' reuse behaviour. The study focused on transition of packaging and observed consumers' behaviour and found a relationship between shopping for goods and disposal of waste packaging.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In their article on customer perception of refillable paper, Lofthouse et al 11 essentially address the value side of design for sustainability. Also, the work on prevention littering by Wever et al 12 and the work on re-use of packaging 13 focus on the value of the packaging. However, these authors did not combine that value perspective with a quantified assessment of the eco-burden.…”
mentioning
confidence: 99%
“…The waste problem is also important because in most EU countries (including Lithuania) only 50 % of packages are recycled or used for energy recovery. Thus, the growing concern about the harmful impact of discarded polymeric packages leads to the researches and developments of polymeric packaging that could degrade more rapidly in the landfills [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%